An Open-Label Observational Trial to Evaluate the Possible Effects of Individualized Homoeopathic Medicines in Symptomatic Nasal Polyp - Aniruddha Banerjee; Birendra Prasad Srivastava; Munmun Koley; Subhranil Saha (Bengal Journal of Otolaryngology and Head Neck Surgery, 2019)
Introduction: Nasal polyps presenting with chronic rhino-sinusitis (CRS) is a commonly encountered condition characterized by nasal obstruction, loss of sense of smell (anosmia), postnasal drip, headache, and sleep disorders. Possibly 60-65% of the populations suffering from CRS has predisposition to nasal polyps. Homoeopathic literature claims to offer successful treatment of nasal polyps; but scarcely subjected to systematic research.